Designing nanomaterials to maximize performance and minimize undesirable implications guided by the Principles of Green Chemistry. (21st August 2015) - Gilbertson, Leanne M.; Zimmerman, Julie B.; Plata, Desiree L.; Hutchison, James E.; Anastas, Paul T.
<x xml:space="preserve">Abstract</x> A sustainable material design framework is proposed that emphasizes the importance of establishing structure–property–function (SPF) and structure–property–hazard (SPH) relationships to guide the rational design of ENMs.